The Influence of Marketing Mix and Customer Relationship Marketing on Marketing Performance of Digital Creative Industry in West Java - Nina Kurnia Hikmawati; Agus Achmad Suhendra; Efrata Denny Saputra Yunus (Sebelas Maret Business Review, 2017)
The creative industries is growing rapidly. The most rapid growth is industry-based creative digital technology. It is influenced by the development of internet technology that has entered various aspects of human life in society and the state. Today, almost all the activities and business processes intersect and take advantage of the internet. This phenomenon is known as a digital transformation, where any business that wants to develop must be connected via internet to be able to reach more consumers through telecommunications technology. However, the performance marketing of digital creative industry currently is not classified as optimal. That's because the problems related to the implementation of the marketing mix and customer relationship marketing are not optimal. Thus this study aims to examine the influence of the marketing mix and customer relationship marketing on marketing performance of digital creative industry in West Java. Data were collected from 50 companies in the digital creative industry in West Java. The results showed the influence of the marketing mix and customer relationship marketing to marketing performance of digital creative industry in West Java.